Wildland-Urban Interface: Key Issues - L. Annie Hermansen-Baez; Jennifer Seitz; Martha C. Monroe (EDIS)
Revised! FOR-202, a 6-page fact sheet by L. Annie Hermansen-Baez, Jennifer Seitz, and Martha C. Monroe, describes key issues gleaned from a series of focus groups conducted by the U.S. Forest Service in 2000, and other related sources. Includes references. Published by the UF School of Forest Resources and Conservation, October 2008.